Process Development of a Liquid-Gated Graphene Field-Effect Transistor Gas Sensor for Applications in Smart Agriculture - Jian Lu; Naoki Shiraishi; Ryo Imaizumi; Lan Zhang; Mutsumi Kimura (Sensors)
A compact, multi-channel ionic liquid-gated graphene field-effect transistor (FET) has been proposed and developed in our work for on-field continuous monitoring of nitrate nitrogen and other nitrogen fertilizers to achieve sustainable and efficient farming practices in agriculture. However, fabricating graphene FETs with easy filling of ionic liquids, minimal graphene defects, and high process yields remains challenging, given the sensitivity of these devices to processing conditions and environmental factors. In this work, two approaches for the fabrication of our graphene FETs were presented, evaluated, and compared for high yields and easy filling of ionic liquids. The process difficulties, major obstacles, and improvements are discussed herein in detail. Both devices, those fabricated using a 3 μm-thick CYTOP® layer for position restriction and volume control of the ionic liquid and those using a ~20 nm-thick photosensitive hydrophobic layer for the same purpose, exhibited typical FET characteristics and were applicable to various application environments. The research findings and experiences presented in this paper will provide important references to related societies for the design, fabrication, and application of liquid-gated graphene FETs.